A Skills-Based Framework for Evaluating Trengkas Proficiency Among TVET Students at Polytechnic Malaysia - Ahmad Azizi, Aziawati; Mohd Razalli, Norsalwati; Hamidon, Nurhafizah; Ahmad, Zainal Ariffin (Research and Innovation in Technical and Vocational Education and Training, 2025)
Trengkas, a shorthand system for the Malay language, is a important  skill for administrative and professional transcription tasks for stenography students. However, only a few studies have examined Trengkas proficiency through a comprehensive skills-based framework. This study fills this gap by assessing students' Speed, Accuracy, and Transcription Efficiency across five major components of skill: Knowledge, Affection, Conation, Sensory Motion, and Active Cognition Ability. Data was collected from 196 polytechnic students using structured questionnaires measuring transcription and cognitive skills that drive accuracy and efficiency of motivational and emotional engagement. Considering the limited opportunities, students have to practice this skill. The findings reveal that the components of the skill-based framework significantly affected Trengkas proficiency. Many students struggle with traditional, real-time dictation; there is a clear need for better pedagogical techniques. The study concludes that a skills-based framework is a useful mechanism for assessing Trengkas proficiency, and adjustments to the curriculum are recommended. Bridging gaps in active cognition and motivation can better prepare students for the demands of the workplace. Thus, future research should incorporate technology into Trengkas training to streamline learning outcomes.